Experimental and numerical study on progressive damage and failure in composite laminates during open-hole compression tests. (June 2021) - Higuchi, R.; Warabi, S.; Yoshimura, A.; Nagashima, T.; Yokozeki, T.; Okabe, T.
Abstract: Progressive damages in the open-hole compression (OHC) tests of composite laminates were experimentally and numerically studied. In the experiment, the failure mechanisms were investigated via in situ microscopy observation, digital image correlation, X-ray radiography, and X-ray computed tomography. Three layups were tested to examine the dependence of progressive damages on the layups. Additionally, numerical simulation was conducted to comprehensively examine the failure mechanisms. In the numerical studies, the simulation scheme, considering the plasticity, kink-band failure, multiple intra-laminar cracks, and delamination, was developed. From the experiment and simulation, it is clarified that the kink-band is initiated and propagated by the combined stress states consisting of longitudinal compression and in-plane shear around the intra-laminar cracks. Therefore, for the high-fidelity OHC simulation in various layups, it is necessary to capture the interaction between kink-band and intra-laminar cracks by considering the combined stress state in the kink-band failure criteria and modeling the multiple intra-laminar cracks.